Analysis digital panoramic radiograph about positions root of maxillary posterior teeth with maxillary sinus floor - Pertiwi, Aprilia Dian; Noerianingsih Firman, Ria; Pramanik, Farina (Faculty of Dentistry Universitas Padjadjaran, 2016)
Introduction: Maxillary sinus floor is a part of the alveolar bone adjacent to the apex of the posterior maxillary teeth that often causes complications in dentistry. Anatomical relationship between the maxillary posterior tooth root and the maxillary sinus floor can be obtained by panoramic radiograph. The purpose of this study is to analysis digital panoramic radiograph about positions root of maxillary posterior teeth’s with maxillary sinus floor by age and gender using. Methods: Research method is descriptive with purposive sampling technique. Study population was taken from archives of patient’s digital panoramic radiograph in Radiography Installation from January to March 2016. 88 samples were obtained from 207 digital panoramic radiographs archives. Results: The result showed that type 3 was dominated by P1 (86.8% right, 88.2% left), type 2 is dominated by P2 (24.7% right, 21% left), type 1 is dominated by M2 in the right (31.2%) and M1 in the left (38.1%). Conclusion: This study concludes that overall, the most commonly found was type 3. Based on the age, type 1 majority occurs in age group of above 49 years old; type 2 in age group of 40-49 years old; and type 3 in age group 30-39 years old, 40-49 years old, and above 49 years old. By gender, type 1 and type 2 are more common in males, while type 3 is more common in female.